Analisis Percepatan Terhadap Biaya Proyek (Study Kasus : Kantor Dinas SKPD Gedung B5 Tenayan Raya) - Jurandi Jurandi; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Project management so important for implementation a project for avoid problem that can create disadvantages for owner or contractor, one of the problems that commonly occur in a project is a estimated cost and timework isn’t fit with the planning. project construction The Construction Project of Regional Work Units Pekanbaru City Government Office late 75 days from contract duration. Work can more fast with 3 ways, alternative overtime work, alternative add more manpower and equipment, and alternative shift system. only work with critical path is working in. analysis result obtained cost of construction acceleration that caused by overtime alternative is Rp. 18,660,148.32, overtime implemented for 3 hours in a day. Workers and equipment additional alternative that adjusted by field requirement result is Rp 30,422,011,240.30 and shift alternative with day and night shift had equal productivity, with construction acceleration that caused by shift alternative is Rp 22,479,247,709.57. In conclusion, the most effective construction acceleration method is overtime alternative, obtained the minimum financial loss and recommended to use for the construction acceleration.Keywords : Management, delay, cost, duration, overtime, work equipment and workers additional.